Electrical conductivity of bismuth doped dysprosia stabilized zirconia as an electrolyte material for SOFC - Raghvendra; Singh P. (My University, 2025)
We report our investigations on structural, thermal and electrical behavior of 10 mol.% dysprosia stabilized zirconia (DySZr) and 2 mol.% Bi2O3-doped dysprosia stabilized zirconia (2BiDySZr) prepared via a solid state ceramic route. Addition of 2 mol.% of Bi2O3 decreased the sintering temperature of DySZr, promoted the growth of zirconia grains and also improved the density. This also supports stabilizing the cubic phase at room temperature. The electrical conductivity was found to increase on account of bismuth doping in DySZr. The activation energies for conduction in DySZr and 2BiDySZr systems were found to be 1.11 and 1.15 eV, respectively in the measured temperature range, indicating the oxygen ion conductivity in the system. The thermal expansion coefficient of the Bi2O3-doped DySZr system was found to match with the other component materials for solid oxide fuel cells. © Carl Hanser Verlag GmbH & Co. KG ISSN 1862-5282.